UJIAN OSCE REGULER BERORIENTASI ERGONOMI MENINGKATKAN KINERJA PENGUJI DI FAKULTAS KEDOKTERAN UNIVERSITAS ISLAM AL-AZHAR MATARAM - ', Iing .; Sutjana, Dewa Putu; Swamardika, Ida Bagus Alit (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic); Vol 1 No 2 (2015): Volume 1 No 2 Desember 2015, 2015)
Regular Objective Structured Clinical Examination  (OSCE) was a clinical skill  test in the Faculty of Medicine Islamic University Al-Azhar Mataram.  Examiner of OSCE in this study was a doctor who was also a lecturer trained in judging student’s clinical skills. The study aimed to know whetherergonomic-oriented regular OSCE by muscle stretching and drinking sweetened tea can improve the performance of examiners in the Faculty of Medicine Islamic University Al-Azhar Mataram. Performance improvement indicators used were decreased complaints of boredom, fatigue and musculoskeletal.Methods used in this study was experimental study with “treatment by subject design”. The study used as many as 18 sample given two treatment which was the first period without the ergonomic intervention involving stretching of the muscle and drinking sweetened tea and the second period was a group with ergonomic intervention. Boredom was measured by a boredom questionnaire.Fatigue, was measured from 30 items of fatigue questionnaire from Japan IFRC(Industrial Fatigue Research Committee).   Skeletal   muscle   complaints was predicted from  Nordic Body  Map  questionnaire.  Data  were  analyzed  bynormality test and t-paired test with significancy level of 5%.The results of this study showed that there was a significant difference(p<0,05) in average score boredom, fatigue and musculoskeletal complaints. The mean boredom score in the first period was 39,724 and in the second period was26,415 with reduction in average boredom score was 33.5 %. Fatigue mean scorein the first period  was 44,050 and the second period was 23,525 with reductionof fatigue score was  46,59 %. Mean musculoskeletal complaints score in the first period was 39,25 and the second period was 14,02 with reduction in mean musculoskeletal complaints score was 64,28 %. 19It can be concluded from this study that ergonomic  intervention by muscle stretching and drinking sweetened tea in the interrupted time of examination process improved the performance of OSCE examiner in terms of boredom, fatigue and musculosceletal complaints in the Faculty of Medicine of Islamic University Al-Azhar Mataram.
Keywords: OSCE, Ergonomic Orientation, Performance